The 'Hierarchy of Truths' in the Thought of John Henry Newman - Ernst, Harold E. (Irish theological quarterly, 2005)
The author argues that Newman exhibits an implicit notion of the hierarchy of truths, as that concept has come to be understood following the Second Vatican Council. He surveys the evolution of the concept's theological understanding from its introduction at Vatican II, then utilizes the structure of this survey as a basis for exploring the congruity of various aspects of Newman's thought with the contemporary theological reception of the conciliar notion of the hierarchy of truths.